Community and Marine Conservation in South Africa: Are We Still Missing the Mark? - Peer, Nasreen; Muhl, Ella-Kari; Janna, Jamila; Brown, Michael; Zukulu, Sinegugu; Mbatha, Philile (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) in South Africa have a long history with currently 5% of the mainland’s ocean territory protected. The MPAs are celebrated and appreciated for their representative coverage of several habitat types and their ecological benefits. However, the story of correlational coastal community exclusion is not one that is often told in the ‘success’ story of South African MPAs. In this review we describe the history of marine conservation in South Africa and examine how the legislation and motivation has evolved since Apartheid. While legislation provides direction in terms of community inclusion, this is rarely the reality as we explore with five case studies. We go on to discuss how top-down governance continues to exclude communities and suggest key lessons drawn from our case-studies that could lead to a more community-involved approach to the ongoing protection and management of our marine habitats for greater conservation success.